An Overview of Electronic Commerce (e-Commerce) - JAIN, VIPIN; MALVIYA, BINDOO; ARYA, SATYENDRA (The journal of contemporary issues in business and government, 2021)
The world economy is witnessing a transition. All companies are transformed into information-based operations through online technologies. The pace of technical transition is so exponential that modern electronic commerce is now making significant shifts in the economic environment, impacting all areas of industry. The Web has expanded companies’ scope. The vast quantity of business information made accessible by the global network that facilitates the gathering of information between firms, a corporation, its clients and the various divisions of a business is increasing exponentially. The information-based virtual value chains for any company cannot be overlooked operationally or strategically. This review article discussed the aspects of electronic commerce including its importance, facilitators, benefits, challenges and scope in the Indian market.